Religious Behavior of Micro, Small, and Medium Enterprises among Muslims in Kudus - Muhamad Mustaqim (Journal of Islamic Studies and Civilization, 2024)
This study aims to explore the relationship between religious behavior and business activities among Muslim Micro, Small, and Medium Enterprise (MSME) entrepreneurs in Kudus Regency. Kudus, as one of the economic hubs in Central Java, shows significant potential in the MSME sector, supported by a majority Muslim population. This research employs a qualitative approach, using primary data collected from 30 MSME entrepreneurs and secondary data from related literature. The findings reveal that the religious behavior of MSME entrepreneurs reflects the integration of religious values into daily life and business practices. Most respondents perform obligatory prayers, as well as additional acts of worship such as Sunnah prayers, Quran recitation, manaqiban, tahlilan, and visits to the tombs of saints. Some entrepreneurs also provide prayer facilities for employees and organize regular religious gatherings to foster spirituality in the workplace.